O plano nacional de educação em direitos humanos: uma ideia de formação escolar cidadã - Silva, Simone Stefani da (2016)
The theme of Human Rights and its close connection with school education becomes an indispensable element in the proposition of public policies in Brazil. In this sense, this work aims to analyze how the National Plan of Education on Human Rights conceives training for citizenship and, more precisely, an education to human rights in school. From historical perspectives that see different generations of human rights in the world and also directly related to the educational field, the research seeks to identify and discuss how the PNEDH features and conceives its objectives in relation to the educational process linked to an education in rights human within Primary education taking aims to distinguish between the understanding of education as a human right and the meaning of human rights education - to be extended to the entire education process. The research is based on literature and document analysis research - and seeks to address some limits and possible consequences of the Plan in the context of the organization of the national basic education.